Optimalisasi Kewarganegaraan Digital melalui Desain Pembelajaran Online - Nisrina Nurul Insani; Siti Hamidah; Widianti Utami Martadinata (Departement of Mathematics Education, 2024)
Digital technology disruption has significantly changed the pattern of life in society, both at the national and global levels, with impacts that can vary, from positive to negative, depending on society's ability to face existing challenges. This is what drives the urgency of digital citizenship to prepare society to face the changing impacts of digital technology disruption. This research aims to reveal the relationship that exists between digital citizenship and learning design in the context of effective online learning strategies. The research method used is a case study with a qualitative approach. Data was collected through interviews, documentation studies, and observations to explore how digital citizenship principles can be integrated in the design of online learning activities. The research results revealed that the principles of digital citizenship, particularly in terms of responsible and ethical online behavior, were successfully integrated into the design of online learning activities. This has a positive impact on increasing student engagement and their learning outcomes in online learning environments. This research makes a significant contribution to increasing understanding of the importance of integrating digital citizenship in the design of effective online learning.